Cohort profile: the National Congenital Anomaly Registration Dataset in England - Danielle Martin; Sarah Stevens; John Broggio; Chloe Johnson; Kate M Fleming; Ben Wreyford; Sylvia Stoianova; Gabriella Melis; Ewoma Obaro; Jennifer M. Broughan; Kay Randall; Nicholas Aldridge; et al. (BMJ Open)
Purpose The National Congenital Anomaly and Rare Disease Registration Service (NCARDRS), part of National Disease Registration Service in National Health Service England, quality assures, curates and analyses individual data on the pregnancies, fetuses, babies, children and adults with congenital anomalies and rare diseases across England. The congenital anomaly (CA) register provides a resource for patients and their families, clinicians, researchers and public health professionals in furthering the understanding of CAs.Participants NCARDRS registers CAs occurring in babies born alive and stillborn, fetal losses and terminations in England. NCARDRS collects data from secondary and tertiary healthcare providers, private providers and laboratories covering fetal medicine, maternity or paediatric services. Data describe the pregnancy, mother, baby and anomaly. Established in 2015, NCARDRS expanded CA registration coverage from 22% of total births in England in 2015 to national coverage, which was achieved in 2018. Prior to 2015, data collection was performed independently by regional registers in England; these data are also held by NCARDRS.Findings to date NCARDRS registers approximately 21 000 babies with CAs per year with surveillance covering around 600 000 total births, the largest birth coverage for a CA register globally. Data on prevalence, risk factors and survival for children with CAs are available. Data have been used in several peer-reviewed publications. Birth prevalence statistics, including public health indicators such as the association with maternal age, infant and perinatal mortality, are published annually. NCARDRS supports clinical audit for screening programmes and service evaluation.Future plans NCARDRS provides a valuable resource for the understanding of the epidemiology, surveillance, prevention and treatment of CAs. Currently, approximately 21 000 new registrations of babies or fetuses with suspected or confirmed CAs are added each year. Identifiers are collected, enabling linkage to routinely collected healthcare and population statistics, further enhancing the value of the data.